INVESTIGATING the EFFECTIVENESS of LEAF ETHANOL EXTRACT GEL PREPARATION RED SPINACH (Amaranthus tricolor L.) in HEALING of BURNS on RATS MALE WHITE (Rattus norvegicus) - Nur Hidayatul Ilmiah (Strada Journal of Pharmacy, 2021)
Red Spinach (Amaranthus tricolor L.) has many health benefits, one of which is in the healing process of burns. The aim of this research was to determine the effectiveness and concentration of ethanol extract of Red Spinach leaves (Amaranthus tricolor L.) which is effective in the healing process of burn wounds in male white rats (Rattus norvegicus). The research method used is experimental. The results of the phytochemical screening of the ethanol extract of red spinach leaves contain flavonoids, alkaloids, saponins and tannins. The effectiveness test in the healing process of burn wounds used 25 experimental animals which were divided into 5 treatment groups, namely negative control group (HPMC base), positive control (Bioplacenton), and extract group with concentration variants of 5%, 10%, and 20%. Observation of the burn wound healing process was carried out by measuring the diameter of the wound on days 2, 4, 6, 8, 10, 12, 14 where the average diameter was calculated as the percentage of burn wound healing. Statistical analysis was carried out using the One Way Anova test with a significant value of p: 0.000 and continued with the LSD test. The results of the study stated that 70% ethanol extract of red spinach leaves had activity in the healing process of burn wounds in male white rats. The concentration dose that was most effective in healing burns in male white rats was 70% ethanol extract of red spinach leaves with a 20% concentration.